(untitled) (Journal of Global Accounting, 2025)
This study explores the relationship between financial literacy, spending behavior, and consumer credit usage among academic staff at Chukwuemeka Odumegwu Ojukwu University (COOU), Igbariam, Nigeria. Using a survey-based methodology, data was collected from 200 respondents, and the relationships among key variables were analyzed using regression models. The findings reveal that higher financial literacy is negatively associated with consumer credit usage, suggesting that individuals with better financial knowledge tend to use credit less frequently. Additionally, spending behavior was found to have a significant positive relationship with credit usage, indicating that individuals who engage in excessive or impulsive spending are more likely to rely on credit. Financial literacy also moderated the relationship between spending behavior and credit usage, suggesting that higher financial knowledge can reduce the negative impact of poor spending habits. Control variables, including income level and marital status, were found to influence credit usage, with higher income earners being more likely to use credit. The study highlights the need for financial literacy programs and spending behavior interventions to improve credit management among Nigerian university staff. The findings provide valuable insights for policymakers, financial institutions, and educators to promote responsible credit usage and financial well-being